2018
DOI: 10.1080/00330124.2017.1416302
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Domestic Water Consumption on the Spanish Mediterranean Coastline

Abstract: During the last decades in the Spanish Mediterranean coastline there has been a great development of low density urban area, as well as a change of the sociodemographic structures, especially in the municipalities that have developed a residential tourism model. Likewise, urban and tourist development have stressed the balance between the availability of water resources and urban water demands, generating situations of scarcity which may be aggravated by climate change. This study identifies the determinants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In contrast to March and Saurí (2010), who found urban density is the most critical variable to explain water consumption, the effects of density in this study, though significant, hardly improve the adjusted R-square of the model (Table 2). Previous studies often found that higher urban density reduces water demand mainly through smaller lot sizes (Fox et al, 2009;Villar-Navascués and Pérez-Morales, 2018). Even though lot size was not available in this study, after controlling for similar factors such as living area and the presence of (a) pool(s) or garden(s), the remaining effect of densities becomes marginal.…”
Section: Spatial Variation In Residential Water Consumptionmentioning
confidence: 61%
“…In contrast to March and Saurí (2010), who found urban density is the most critical variable to explain water consumption, the effects of density in this study, though significant, hardly improve the adjusted R-square of the model (Table 2). Previous studies often found that higher urban density reduces water demand mainly through smaller lot sizes (Fox et al, 2009;Villar-Navascués and Pérez-Morales, 2018). Even though lot size was not available in this study, after controlling for similar factors such as living area and the presence of (a) pool(s) or garden(s), the remaining effect of densities becomes marginal.…”
Section: Spatial Variation In Residential Water Consumptionmentioning
confidence: 61%
“…Industrial water consumption is primarily determined by economic growth, industrial structural adjustments, and technological progress. Existing studies on domestic water use mainly focus on household domestic water use and its influencing factors at the micro level [7,19,21,[29][30][31][32][33]. Research data were always obtained through questionnaire survey, water-use diary, field observation and interview [34].…”
Section: Introductionmentioning
confidence: 99%
“…This substantial seasonal imbalance between water availability and demand has led to the development of a very dense network of dams and hydraulic infrastructure. Further, the Spanish Mediterranean coast has generally shown an increase in urban and tourist-related development in recent decades causing additional water scarcity, impacts that are likely to be intensified by climate change [25]. Under this socioeconomic context, the Mediterranean regions should take special care in the management of their water resources, as shown in [26,27].…”
Section: Introductionmentioning
confidence: 99%